EVALUASI KURIKULUM PENDIDIKAN AGAMA ISLAM - Muhammad Syaikhul Lubib; Muhammad Abu Khasan; Sa’ida Muhimmatul ‘Ula; Imam Junaris (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the evaluation of the Islamic Religious Education (PAI) curriculum, including the definition, objectives, principles and approaches, as well as the stages of evaluation. The method used is library research with descriptive- analytical analysis. The results show that PAI curriculum evaluation is a systematic, planned, and continuous process that does not only focus on final outcomes but also on the process, context, input, and impact of learning. The objectives of evaluation include measuring learning achievement, identifying supporting and inhibiting factors, and continuous quality improvement through the Tyler and CIPP models. The principles of evaluation include continuity, comprehensiveness, objectivity, transparency, accountability, and the foundation of Islamic values. The stages of evaluation consist of planning, data collection, data analysis, interpretation of results, and follow-up.